2021
DOI: 10.1177/00916471211011598
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Ideologies, Marital Satisfaction, and Eudaimonic Well-Being in Evangelical Women

Abstract: Recent research has demonstrated that egalitarian gender role ideologies are associated with higher marital satisfaction and higher psychological well-being. However, there has been little research investigating whether gender role ideologies in Evangelical populations follow these same trends. The current study examined how gender role ideologies in an Evangelical population are related to marital satisfaction and eudaimonic well-being, as well as the role of locus of control in these relationships. Three hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“… 51 Evidence shows that this continuous disagreement often results in low marital satisfaction and violence is often used as a way of dealing with the conflicts or resolving the differences. 52 - 54 However, study shows that these forms of violence can be resolved through counselling like systematic couples therapy and relationship enhancement education and counselling and thus recommends reducing physical, psychological and sexual violence against women during pregnancy in LMIC settings. 55 …”
Section: Discussionmentioning
confidence: 99%
“… 51 Evidence shows that this continuous disagreement often results in low marital satisfaction and violence is often used as a way of dealing with the conflicts or resolving the differences. 52 - 54 However, study shows that these forms of violence can be resolved through counselling like systematic couples therapy and relationship enhancement education and counselling and thus recommends reducing physical, psychological and sexual violence against women during pregnancy in LMIC settings. 55 …”
Section: Discussionmentioning
confidence: 99%
“…There is also a growing consensus about how well-being should be measured [5]. Studies found that people with a higher sense of well-being tend to be more successful in other areas of life such as health, marriage, social relationships, and so on [6,7]. Happiness is a goal that people pursue.…”
Section: Introductionmentioning
confidence: 99%